The Bonding Effect of Deferred Compensation: Worker Separations from a Large Firm in Early Transition Russia - Mikhail Ananyev; Thomas Dohmen; Hartmut Lehmann (Institute of Labor Economics (IZA), 2020)
Deferred payments, as implicit contracts, are predicted to bind workers to firms as long as workers believe that firms adhere to these implicit contracts. We employ a unique personnel data set from a Russian manufacturing firm to investigate whether wage arrears, delayed payments of wages, induce bonding effects. We find that workers' separation rates decrease dramatically when workers experience wage arrears, providing evidence for the bonding effects of deferred compensation schemes. After workers are repaid nominal wages, but have suffered real wage losses due to unexpectedly high inflation, we observe that workers affected by wage arrears again become much more likely to separate during and after the repayment period of a second episode of wage arrears, providing evidence for the weakening of the bonding effect after the firm's reputation for adequately compensating for deferred payments has been jeopardized.
Keywords: J30; J63; M52; P23; 330; deferred compensation; worker turnover; wage arrears; personnel data; Russia